Journalists and Editors: Political Proximity as Determinant of Career and Autonomy. (October 2019) - Ceron, Andrea; Splendore, Sergio; Hanitzsch, Thomas; Thurman, Neil
Political economy suggests that media owners try to influence the process of media production by providing career incentives to like-minded journalists and adjusting the level of professional autonomy granted to them. Accordingly, we analyze whether the political distance between editors and journalists (i.e., reporters) affects the careers of journalists in terms of rank and salary, as well as their perceived professional autonomy. We hypothesize that editors reward and allow freedom to journalists whose political viewpoints coincide more precisely with their own. Political proximity to editors should lead to a better salary and rank for reporters and to a stronger perception of editorial autonomy among reporters. We tested our hypotheses through statistical analysis using data from the Worlds of Journalism Study. We analyzed the answers of 3, 087 journalists interviewed between 2012 and 2016 in six European countries: Germany, Ireland, Italy, the Netherlands, Spain, and the United Kingdom. The results support our hypotheses. The analysis reveals a polarization of media outlet editors, and robust results were achieved via a measure of political proximity that takes into account the particular influence of left-leaning and right-leaning editors. Such partisan leaning, however, seems less relevant in countries belonging to Hallin and Mancini's Atlantic model.